THE EFFECT OF IMPLEMENTATION OF THE INDONESIAN INTERNATIONAL ORGANIZATION FOR STANDARDIZATION (SNI ISO) (9001:2015) QUALITY MANAGEMENT SYSTEM IN IMPROVING SALES - Muliani, Muliani; Romadhoni, Buyung; Rizal, Samsul (Jurnal Ekonomi Balance, 2018)
This research uses quantitative research methods. Data obtained from primary data is through the distribution of questionnaires. Research respondents were all employees of PT. Wijaya Karya Beton. Tbk (Regional Sales VI) Makassar. The questionnaire was processed using the SPSS 22 application. This research is expected to be input for PT. Wijaya Karya Beton. Tbk (Sales Region VI) Makassar to apply SNI ISO (9001: 2015) well. The results showed that the implementation of the ISO ISO Quality Management System (9001: 2015) had a significant positive effect on increasing sales of PT. Wijaya Karya Beton, Tbk (Sales Region VI) Makassar. Judging from the value of the determinant coefficient shown by Adjusted R square that is equal to 0.960 shows that 96.0% this means that 96.0% of the implementation of the ISO ISO Quality Management System (9001: 2015) has a significant positive effect in increasing sales of PT. Wijaya Karya Beton. Tbk (Sales Region VI) Makassar while 4% is explained by other factors not examined in this study.